Final answer:
To simplify the expression, we factored the numerator and denominator, canceled common factors, and obtained the simplified form 2(x + 2) over (x - 10).
Step-by-step explanation:
To simplify the given rational expression, 2x² + 20x + 32 over x² - 2x - 80, we need to factor both the numerator and the denominator. Factoring the numerator:
2x² + 20x + 32 = 2(x² + 10x + 16)
2(x + 8)(x + 2) (by factoring x² + 10x + 16)
Factoring the denominator:
x² - 2x - 80 = (x - 10)(x + 8)
Now the expression looks like:
2(x + 8)(x + 2)
-------------- =
(x - 10)(x + 8)
We can cancel out the common factor of (x + 8):
2(x + 2)
--------- =
(x - 10)
So, the simplified form is:
2(x + 2)
-------- = (x - 10)